TETRAPROPYLAMMONIUM HYDROXIDE AS A ZINC DENDRITE GROWTH SUPPRESSOR FOR RECHARGEABLE AQUEOUS BATTERY - Kurmanbayeva, Indira; Rakhymbay, Lunara; Korzhynbayeva, Kuralay; Adi, Akylbek; Batyrbekuly, Dauren; Mentbayeva, Almagul; Bakenov, Zhumabay (Frontiers Media, 2020)
Zinc metal is widely used as an anode in various aqueous systems. However, zinc anode suffers from the dendrite formation on the surface upon cycling leading to a poor cyclability of a cell and its termination due to short circuit. In this work, the effect of tetrapropylammonium hydroxide (TPAH) was studied as an electrolyte additive for aqueous Zn//ZnCl2 + LiCl//LiFePO4 battery. TPAH additive prolongs the battery cycle life depending on its concentration (0.01–0.1 M). The better capacity retention over 350 cycles was observed for a symmetrical Zn//ZnCl2 + LiCl//Zn cell with 0.05 M TPAH whereas without additives the cell worked for only 110 cycles. The mechanism of TPAH influence on capacity retention is proposed based on the results of SEM and XRD analysis of the Zn anode and FTIR and NMR studies of the electrolyte. The XRD patterns of the negative electrode of the cell with TPAH indicates that zinc was preferentially deposited in a highly oriented (002) direction, which is more resistant against dendrite formation. These differences in deposited structure of Zn dendrites were confirmed by SEM images as well. FTIR and NMR spectra showed that TPAH decomposes to propylamine (RnN+H) and propene during cycling. TPAH also has an effect on the size and uniform distribution of Zn growth sides.
Keywords: tetrapropylammonium hydroxide; zinc anode; zinc dendrites suppression; aqueous electrolyte; lithium-ion battery; Research Subject Categories::TECHNOLOGY